First-principles study on the structural and electronic properties of single-layer MoSi2N4 - Nguyen, Cuong Q.; Le, Thi Thu Phuong; Nguyen, Chuong V. (Hue University Journal of Science: Natural Science, 2022)
Motivated by the successful exfoliation of a novel two-dimensional MoSi2N4 materials, in this work, we investigate the structural and electronic properties of a novel single-layer MoSi2N4 and the effect of strain engineering by using the first-principles calculations based on the density functional theory. The single-layer MoSi2N4 has a hexagonal structure with a space group of P6m1, which is dynamically stable. The material exhibits a semiconducting characteristic with an indirect band gap of 1.80/2.36 eV calculated by using the PBE/HSE functional. The conduction band minimum at the K point of the material originates from the Mo atom, while its valence band maximum at the G point is contributed by the hybridization between the Mo and N atoms. The electronic properties of the single-layer MoSi2N4 can be modulated with strain engineering, giving rise to a transition from a semiconductor to a metal and tending to a change in the band gap. Our results demonstrate that the single-layer MoSi2N4 is a promising candidate for electronic and optoelectronic applications.